Analysis Analysis of the Appropriate Level of Economics Textbooks Used by Class X Students of North Kuta 1 Public High School: Economics Textbooks Used by Class X Students of North Kuta 1 Public High School - Kulla, Linda (Arthaniti Studies, 2023)
The problem of this research is how the feasibility of the contents of textbooks for class X students of economics with an independent curriculum published by CV Putra Nugraha whose book is Maryani at SMA Negeri 1 Kuta Utara. The purpose of this study was to determine the feasibility of the contents of an economics textbook for class X students on an independent curriculum published by Putra Nugraha cv Putra Nugraha whose book Maryani at SMA Negeri 1 North Kuta through a textbook assessment instrument. This research uses a descriptive method. The source of the data in this study was the handbook for class X economics students with an independent curriculum published by Putra Nugraha whose book Maryani at SMA Negeri 1 Kuta Utara, with data collection techniques in the form of documentation and interviews. based on the results of the book assessment instrument for (1) the feasibility of the content through this textbook assessment instrument, a score of 90% was obtained which was classified as very feasible, (2) the feasibility of the language component through this textbook. assessment instrument. a score of 98.21% was obtained and the feasibility level was very feasible, (3) the feasibility of the presentation component through this textbook assessment instrument obtained a score of 92.18% and it was very feasible. (4) the feasibility of the graphic component in this student's textbook scored 83.33% and was very feasible.